A reason for apatheism - Gonçalves, Conrado Vasconcelos (International journal for philosophy of religion, 2024)
In a recent paper, Trevor Hedberg and Jordan Huzarevich assessed a number of objections against practical apatheism, concluding that they are either unsuccessful or at least very controversial. The aim of this discussion note is to contribute to their discussion by presenting and analysing a short argument for a reason in favor of apatheism; one that appeals to a particular universalist formulation of the thesis of theodical individualism. After briefly introducing a distinction between a particular and a universal version of apatheism, I present the argument, assess its merits in light of some objections to it, I conclude that at least one reason in favor of a particular practical apatheistic position is warranted by it. Finally, I suggest some alternative reasons that could be advanced in favor of apatheism, and I distinguish between strong and weak forms of apatheism.